Pheochromocytoma Presenting as Testicular Pain: An Unusual Case Report - Jinal K. Patel; Varun Reddy; Gauthier Stepman; Debra Angelo; Johnathan Frunzi (Case Reports in Endocrinology)
Pheochromocytoma (PCC) is a rare catecholamine-secreting tumor that arises from chromaffin cells of the adrenal medulla which are derived from the neural crest. This report illustrates a 51-year-old Caucasian male with a history of hypertension diagnosed two years ago who presented to the hospital due to acute onset of right testicular pain of 3-day duration. Laboratory results and imaging revealed a presumptive diagnosis of PCC. The patient had undergone robot-assisted laparoscopic right adrenalectomy 14 days after being diagnosed with PCC due to perioperative management with phenoxybenzamine. The final pathology report revealed a PCC. At follow-up two weeks after discharge, the patient reported complete resolution of his testicular pain.